(untitled) (Journal of Environmental Microbiology and Toxicology, 2023)
The breakdown of sodium dodecyl sulphate (SDS) in contaminated environments is crucial for reducing its ecological impact. We examined the influence of various environmental parameters on the growth and SDS degradation efficiency of Pseudomonas sp. strain UPM-Langkawi 2. The study explored the effects of temperature, pH, nitrogen sources, SDS concentration, and heavy metal presence on Pseudomonas sp. growth and activity. Growth rates were analyzed across temperatures from 20 to 50°C, pH values from 6.5 to 7.5, and various nitrogen sources (ammonium sulphate, ammonium chloride, potassium nitrite, and potassium nitrate) in BS media supplemented with SDS. SDS concentrations ranging from 0.1 to 2.5 g/L and heavy metals at 1 mg/L were also tested. Optimal growth and SDS degradation occurred at temperatures between 25 and 35°C and a pH range of 6.5 to 7.5. Ammonium sulphate at 5 g/L was identified as the most effective nitrogen source for supporting bacterial growth. Pseudomonas sp. achieved the highest growth at SDS concentrations between 0.75 and 1.5 g/L. Heavy metals significantly influenced bacterial growth, with mercury showing the most substantial inhibitory effect, followed by silver, copper, and chromium. Environmental parameters critically influence the biodegradation potential of Pseudomonas sp. Optimizing these conditions can enhance SDS degradation, offering a viable solution for bioremediation in SDS-polluted sites. Future research should focus on detailed kinetic modeling and field applications to validate these findings under natural conditions.